The International Financial Architecture issues in Argentina - Frenkel, Roberto (1999)
It seems difficult to find any country more deeply involved in the IFA motivations and issues than Argentina. There should be a natural attraction in this country for international steps that could contribute to the stabilization of the financial markets. However, no discussion has taken place in the country so far and rarely any mention of the IFA initiatives and meetings can be found. This seemingly paradoxical situation is related to the Convertibility regime prevailing in Argentina. The paper explores the features of the economic performance, the pattern of public discussion and the motivations of Government positions. The conclusion stresses that the participation of the Argentine Government in the IFA initiatives tended to be passive and conservative